CXCR4 and RANK Combination as a Predictor of Breast Cancer Bone Metastasis in Indonesia - Erwin D Yulian; Sonar S Panigoro; Bajuadji Sudijono; Walta Gautama; Primariadewi Rustamadji; Ricky Dosan (Journal of Surgery and Surgical Research - Peertechz Publications, 2021)
Background: Breast cancer has the highest prevalence and incidence among cancers in women. Moreover, it is the most prevalent among all other cancers in Indonesia. Bone metastasis results in higher incidence, better overall survival, but requires higher-cost treatments than visceral metastasis. Therefore, an early predictor of bone metastasis is needed to make early interventions to be efficiently given. Instead of other biomarkers of bone metastasis, CXCR4 and RANK are highly expressed in breast cancer and correlate with bone metastasis. Hence this study is expected to prove the potential of CXCR4 and RANK combination as a predictor of breast cancer bone metastasis. Methods: In a case-control study, CXCR4 and RANK immunohistochemistry tests were done in 58 stage I-IV breast cancer Indonesian subjects. Association between marker combinations and incidence of bone metastasis was analyzed. Then, the diagnosis accuracy values were calculated. Moreover, its associations with clinicopathological factors were also examined.  Results: There was a significant association of the highly expressed CXCR4 and RANK combination with bone metastasis (P <0.01). Besides, the combination of CXCR4 and RANK detections resulted in 100% sensitivity and 66% specificity in predicting bone metastasis. Breast cancer's stage was significantly associated with CXCR4 and RANK expressions combination (P<0.01). Conclusions: A combination of CXCR4 and RANK expressions could act as a screening method to predict the bone metastasis in breast cancer.